A discourse on the potential of crowdfunding and Islamic finance in the agricultural sector of East Java, Indonesia - Mohd Thas Thaker, Hassanudin; Khaliq, Ahmad; Sekaran, K. Chandra; Mohd Thas Thaker, Mohamed Asmy (Faculty of Economics, Universitas Islam Indonesia, 2020)
Literature evidence on the transformation transpires agriculture sector in East Java for the last 5 to 10 years. The contribution of the agricultural sector towards East Java gross domestic product (GDP) in 2008 recorded at 16.55%, however, shrinks to 13.75% in 2015. This statistic shows the regressed contribution of the agriculture sector in comparison to other economic sectors. One common view that linked to shrinking in credit composition is due to the lack of credit accessibility for the sector. Given that, this paper attempts to propose a viable financing model to develop the agricultural sector in East Java known as Integrated Agricultural Land Crowdfunding Model (IALCM) using Islamic financing instruments through a crowdfunding platform. This model is expected to offer farmers in East Java to meet theirliquidity constraints and the Indonesian government to accelerate social entrepreneurship innovation with conceivable recommendations forthe development of agricultural sector in East Java